Digital subtraction angiographic characteristics of progression of moyamoya disease 6 months prior to surgical revascularisation. Issue 1 (27th February 2020) - Ge, Peicong; Zhang, Qian; Ye, Xun; Liu, Xingju; Deng, Xiaofeng; Wang, Jia; Wang, Rong; Zhang, Yan; Zhang, Dong; Zhao, Ji Zong
Abstract : Background: Evidence on the natural angiographic course of moyamoya disease (MMD) is lacking. It takes about 6 months for waiting for revascularisation surgery. The issue of when to perform subtraction angiography (DSA) for follow-up remains unclear. We investigated the natural course of MMD by DSA and attempted to determine the best interval to perform the follow-up DSA. Methods: This is a single-centre cohort study of Chinese MMD inpatients treated from 1 January 2015 to 31 August 2019. Their angiographic findings were evaluated on Suzuki stage and collateral circulation between two follow-ups of the same hemisphere. Results: A total of 110 patients who met the criteria were enrolled in this study. After a median 6 months follow-up, five patients (4.5%) had progression, four females and one male. Time interval of progression ranged from 4 to 137 months with a mean of 61.4 months. Of five patients with progression, four had unilateral lesion (two ipsilateral and two contralateral) and one had bilateral lesions. Collateral circulation was changed in three of five patients. Conclusions: The angiographic evidence of progression in MMD was rare in the short-term follow-up, and most patients with progression had initial unilateral involvement. DSA re-examination may be not needed in patients with bilateral MMD, but needed in unilateral MMD.